A robust and efficient numerical finite element method for cables. (9th July 2020) - Bertrand, C.; Acary, V.; Lamarque, C.‐H.; Ture Savadkoohi, A.
Summary: Numerical simulation of cable systems remain delicate due to their geometrical nonlinearity and also to their intrinsic unilateral constitutive law. Indeed Finite Element approaches (if not implemented carefully) fail to predict accurate equilibrium for cable structures. The major issue to be addressed is the ill‐conditioning, starting configuration and wrong choice of descent direction during iterative methods. An iterative scheme based on Finite Element Method is presented to overcome this issue, even with large number of elements.